Føreren fra Lendum - Pedersen, Lars Schreiber (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
Lars Schreiber Pedersen: The Führer from Lendum In writer Erik Aalbæk Jensen’s well-known homeland novel from Vendsyssel Perleporten (The Pearl Gate) from 1964, the figure “Kratholmmanden” (the Kratholm man), is a local farm owner and Nazi leader, who with mixed success tries to win his local area’s residents over to the cause of National Socialism. Erik Aalbæk Jensen’s “Kratholmmand” character was based on Christian Mikkelstrup. During 1934–44, Mikkelstrup was a member of the National Socialist Workers’ Party of Denmark (DNSAP) and from 1935–44 he functioned as the party leader in Horns Herred in north east Vendsyssel. Despite his passionate engagement for the cause during his 10 years in the service of the party, Mikkelstrup was only able to convince a few local residents about the joy of National Socialism. DNSAP never gained any importance in north east Vendsyssel. The local party division in Lendum, which held its meetings in Mikkelstrup’s home, numbered 20–25 members at its height. Mikkelstrup was not solely to blame for the lack of support for the party in his local area. Both he and his fellow believers fought a battle that was impossible to win. The majority of local residents, like the rest of Denmark, at no point wanted to know about DNSAP – which the county council elections in 1935 and the national elections in 1935, 1939 and 1943 clearly showed – and even a leader with a bigger profile than Mikkelstrup, who was neither much of a writer or a speaker, would hardly be likely to attract more members to the party from the region. Together with a number of dissatisfied DNSAP members, he left the party in 1944 and joined the newly-formed Nazi party “Dansk National Samling”, in which however, he did not make much of an impact. With the Liberation of Denmark in May 1945, he was arrested by the resistance movement and was subsequently found guilty of passing on information to the German Security Service (Sicherheitsdienst), which had been based in Aalborg during the occupation. He received a sentence of 18 months imprisonment. He stayed faithful to his National Socialist beliefs after the war but after his release from the prison camp at Kragskovhede in August 1946, he devoted his work to running his farm at Lendum in Vendsyssel. Christian Mikkelstrup died in 1971.